123k views
2 votes
Tayler tried to evaluate the expression (22-5\times3) + 6(22−5×3)+6left parenthesis, 22, minus, 5, times, 3, right parenthesis, plus, 6. Her work is below. \begin{aligned} &\phantom{=}(22-5\times 3) + 6\\\\ \text{Step }1:\quad&=(22 -15) + 6 \\\\ \text{Step }2:\quad&=7 + 6 \\\\ \text{Step }3:\quad&=1 \end{aligned} Step 1: Step 2: Step 3: ​ =(22−5×3)+6 =(22−15)+6 =7+6 =1 ​

User Everth
by
5.4k points

1 Answer

1 vote

Explanation:

Given the expression that Tayler tried to evaluate as:


(22-5*3) + 6

We will solve this equation using PEDMAS

Multiplication before addition and subtraction

On solving:


Step \ 1\\= (22-5*3) + 6\\= (22-(15)) + 6\\\\Step\ 2\\= (22-15) + 6\\\\Step \ 3\\= 7+6\\= 13

From the steps above, we can see that Tayler made an error in step 3 by taking the difference of 7 and 6 and arriving at 1 instead of summing up to get 13 as shown above.

User Neonidian
by
5.6k points